Gametocidal Factor Transferred from Aegilops geniculata Roth Can Be Adapted for Large-Scale Chromosome Manipulations in Cereals - Kwiatek, Michał T.; Wiśniewska, Halina; Ślusarkiewicz-Jarzina, Aurelia; Majka, Joanna; Majka, Maciej; Belter, Jolanta; Pudelska, Hanna (Frontiers in Plant Science, 2017)
Segregation distorters are curious, evolutionarily selfish genetic elements, which distort Mendelian segregation in their favor at the expense of others. Those agents include gametocidal factors (Gc), which ensure their preferential transmission by triggering damages in cells lacking them via chromosome break induction. Hence, we hypothesized that the gametocidal system can be adapted for chromosome manipulations between Triticum and Secale chromosomes in hexaploid triticale (×Triticosecale Wittmack). In this work we studied the little-known gametocidal action of a Gc factor located on Aegilops geniculata Roth chromosome 4Mg. Our results indicate that the initiation of the gametocidal action takes place at anaphase II of meiosis of pollen mother cells. Hence, we induced androgenesis at postmeiotic pollen divisions (via anther cultures) in monosomic 4Mg addition plants of hexaploid triticale (AABBRR) followed by production of doubled haploids, to maintain the chromosome aberrations caused by the gametocidal action. This approach enabled us to obtain a large number of plants with two copies of particular chromosome translocations, which were identified by the use of cytomolecular methods. We obtained 41 doubled haploid triticale lines and 17 of them carried chromosome aberrations that included plants with the following chromosome sets: 40T+Dt2RS+Dt2RL (5 lines), 40T+N2R (1), 38T+D4RS.4BL (3), 38T+D5BS-5BL.5RL (5), and 38T+D7RS.3AL (3). The results show that the application of the Gc mechanism in combination with production of doubled haploid lines provides a sufficiently large population of homozygous doubled haploid individuals with two identical copies of translocation chromosomes. In our opinion, this approach will be a valuable tool for the production of novel plant material, which could be used for gene tracking studies, genetic mapping, and finally to enhance the diversity of cereals.